Impact of lubiprostone on gastric-emptying profile and the possible effect of concomitant domperidone in healthy adults - Okamura, Takayuki; Yamamoto, Takatsugu; Kimura, Satoshi; Miki, Atsushi; Abe, Koichiro; Kita, Hiroto (Int. Journal of Clinical Pharmacology and Therapeutics, 2017)
Lubiprostone is effective for patients with chronic constipation. This agent sometimes causes upper gastrointestinal symptoms, such as nausea, which is one of the chief reasons for discontinuation. However, the etiology of and strategy against bothersome gastrointestinal symptoms of lubiprostone remain unclear. The goal of this study was to investigate the influence of lubiprostone on the gastric-emptying profile of healthy adults. The effect of domperidone on gastric emptying and gastrointestinal symptoms after lubiprostone administration were also assessed. 80 healthy male participants underwent C acetate breath testing to evaluate gastric emptying. The test meal comprised 200 kcal of a standard liquid nutrient. Each participant underwent 3 random breath tests with: 1) no premedication; 2) 24 µg of lubiprostone 30 minutes prior to the study; and 3) 24 µg of lubiprostone plus 10 mg of domperidone 30 minutes prior to the study. Gastrointestinal symptoms (heartburn, regurgitation, epigastric pain, fullness, distress feeling) during testing were evaluated using a 7-point scoring system. Gastric emptying was significantly delayed by the administration of lubiprostone. Among all 8 subjects, 4 reported heartburn after taking lubiprostone, whereas this symptom was not found when subjects received concomitant domperidone. However, gastric emptying showed little change between lubiprostone alone and lubiprostone plus domperidone. Lubiprostone delayed gastric emptying of liquid in healthy adults, which could be associated with the gastrointestinal symptoms caused by the agent. Domperidone seemed effective against such gastrointestinal symptoms after administration of lubiprostone. This effect seemed unrelated to gastric motility. .